Increased circulating levels of SP-D and IL-10 are associated with the development of disease severity and pulmonary fibrosis in patients with COVID-19 - Pan, Xin; Huang, Zhisheng; Tao, Ningning; Huang, Chuanjun; Wang, Shanshan; Cheng, Zuowang; Fan, Ruyue; Liu, Shuai (Frontiers in Immunology, 2025)
BackgroundPatients with severe COVID-19 can rapidly develop acute respiratory distress syndrome (ARDS), which further increases the risk of developing pulmonary fibrosis. The exact role of macrophage polarization and different cytokine production in the pathophysiology associated with COVID-19 induced ARDS or pulmonary fibrosis is unknown. It is necessary to identify potential biomarkers that can predict the progress of pulmonary fibrosis or other adverse consequences.MethodsWe analyze the plasma samples obtained from healthy individuals and COVID-19 patients who were stratified according to the disease severity and fibrotic-like changes on chest computed tomography (CT) scans. Surfactant Protein D (SP-D), Matrix Metalloproteinase 8 (MMP8), Krebs von den lungen-6 (KL-6), Angiotensin‐Converting Enzyme 2 (ACE2), and macrophage polarization-related biomarkers were determined by ELISA. Data were collected and evaluated using regression models and receiver operating characteristic (ROC) curves.ResultsThe plasma levels of SP-D, MMP8 in patients with ARDS were higher than those of non-ARDS patients. Patients with pulmonary fibrosis had higher plasma levels of SP-D compared to those without fibrotic changes. Among the biomarkers indicative of macrophage polarization, compared to non-ARDS patients, a significant increase in IL-10, Inducible nitric oxide synthase (iNOS), and Arginase-1 (Arg-1) were observed in ARDS patients, while Tumor necrosis factor-α (TNF-α) was decreased. The plasma level of IL-10 was also elevated in patients with fibrotic changes on CT, and was positively correlated with ACE2 and Arg-1. ROC curve results uncovered that SP-D showed higher efficacy in predicting pulmonary fibrosis and ARDS compared to other inflammatory markers. And IL-10 had similar predictive value with traditional inflammatory indicators such as CRP and PCT.ConclusionSP-D and IL-10 exhibited certain predictive abilities for the development of ARDS and pulmonary fibrosis in patients with COVID-19. The determination of these cytokines upon admission is crucial for evaluating the prognosis of COVID-19 patients.